(untitled) (Academia Science Repository, 2023)
The problem of correlation between literary fairy tale and fantasy at different levels of poetics is studied. Among the common features, the nature of the miraculous and the principles of creating images of heroes are highlighted. The second nature of fantasy works in relation to folklore texts and the tendency to the formation of individual author’s myths are considered as distinctive features of fantasy.